Pengampunan bagi Pemulihan Korban Kekerasan dalam RumahTangga - Costantinus Ponsius Yogie Mofun (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2023)
Violence always creates victims. In cases of domestic violence, as in this study, the victims are those who are considered inferior, namely women and children. Victims experience various forms of violence, such as physical, psychological, and social violence from their surroundings. Wounded and traumatic experiences become a kind of walled-in space, which for victims can protect them from experiences of violence, but at the same time unconsciously it becomes a prison that confines freedom and opportunities to achieve happiness and recovery in life. This research offers a theological perspective on forgiveness for the recovery of victims of domestic violence. Using qualitative research methods, data were collected and analyzed through field research, in-depth interviews, and literature analysis related to the theology of forgiveness in the Christian tradition. This research came to the conclusion that violence always leaves wounds and trauma for its victims. The theology of forgiveness reconstructs closed spaces in traumatic experiences into open spaces to welcome the restoration of life for victims. From the perspective of Christian theology, the God who is trusted is a God who remembers, forgives, and delivers.